MENELAAH PELAKSANAAN PENGANGKATAN HAKAM PADA PERKARA SYIQAQ DI PENGADILAN AGAMA INDONESIA DAN MAHKAMAH SYAR’IYAH MALAYSIA - Huzaimah, Arne (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Syiqaq is a constant dispute and quarrel between husband and wife. To overcome the problem of syiqaq, then Allah SWT has arranged it directly in the Qur'an, the letter an-Nisa (4) verse 35, namely by adopting the hakam that comes from the family of each party to reconcile the two husband and wife. The implementation of the appointment of the rights applied in the procedural law of the religious court in Indonesia is not imperative, it all depends on the judge's judgment. Hakam in the Indonesian Religious Court only functions to reconcile the two parties (husband and wife) who are at loggerheads and not the authority to decide. So Hakam only serves as a mediator not an arbitrator. At the Malaysian Syar'iyyah Court, Hakam must obtain full authority from his principal. Husband may give full authority to the husband Hakam to pronounce divorce to his wife before the Court, and the wife can give full power to his wife Hakam to do khuluk or accept Lafaztalak before the Court. keywords: Hakam, Pengadilan Agama, Mahkamah Syar’iyyah